Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3892/or.2016.4953
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3A contributes to the invasion and metastasis of gastric cancer cells

Abstract: CXCR3, belonging to CXC chemokine receptors, has been identified to be overexpressed in various kinds of tumors. There are three mRNA variants of CXCR3 (CXCR3A, CXCR3B and CXCR3alt) in human cells. The functions of major CXCR3 isoforms (CXCR3A, CXCR3B) have been reported in some tumors including prostate and breast cancer. However, the effects of CXCR3A and CXCR3B on gastric cancer cell progression remain unknown. The present investigation found that CXCR3A mRNA level was upregulated but CXCR3B mRNA level was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 27 publications
(28 reference statements)
3
29
0
Order By: Relevance
“…CXCR3B was also able to respectively bind to its ligands CXCL10 and CXCL4 to exert their anti‐proliferative activity and anti‐migratory response, and promote necrosis in n renal cell carcinoma cells . Whereas an increased expression of CXCR3A enhanced the progressive capacity of prostate cancer cells and gastric cancer cells . In line with these findings, the results presented in this study also showed that an overexpression of CXCR3A and CXCR3B respectively increased and reduced the progressive capacities of CRC cells in term of cell proliferation, migration, and invasion, along with a decrease and an increase of cleaved‐Caspase 3 protein in CRC tumor tissues, and tumorigenicity in nude mice.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…CXCR3B was also able to respectively bind to its ligands CXCL10 and CXCL4 to exert their anti‐proliferative activity and anti‐migratory response, and promote necrosis in n renal cell carcinoma cells . Whereas an increased expression of CXCR3A enhanced the progressive capacity of prostate cancer cells and gastric cancer cells . In line with these findings, the results presented in this study also showed that an overexpression of CXCR3A and CXCR3B respectively increased and reduced the progressive capacities of CRC cells in term of cell proliferation, migration, and invasion, along with a decrease and an increase of cleaved‐Caspase 3 protein in CRC tumor tissues, and tumorigenicity in nude mice.…”
Section: Discussionsupporting
confidence: 86%
“…The alternative splice variants of CXCR3 exhibit differential roles in inflammations and cancers by selectively activating different signaling pathways . In this regard, CXCR3A and CXCR3B are generally considered to exert opposite functions in cancers, that is, the CXCR3A mediates signals to promote cancer cell proliferation, survival, migration and invasion, and angiostatic effects in tumors; while the CXCR3B induces signaling to suppress cancer cell growth and progression . Therefore, CXCR3 have been recognized as a prognostic marker and a therapeutic target for patients with solid tumors, including gastric cancer, prostate cancer, breast cancer, and the CRC …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7, 8] The axis for metastases facilitates the migration of CXCR3 expressing cancer cells to ligand rich metastatic sites. As CXCR3-A plays a key role in metastasis,[51] treatment targeting only CXCR3A, not CXCR3B and CXCR3-alt, in the CXCL9, -10, -11/CXCR3 axis could be effective in metastatic disease.…”
Section: Cxcl9 Cxcl10 Cxcl11/cxcr3 Axis For Immune Responsementioning
confidence: 99%